Prelacteal feeding practices with stunted in infants - Nabila Nuary Zefanya; Ade Devriany; Zenderi Wardani; Eri Virmando; Teuku Salfiyadi (AcTion: Aceh Nutrition Journal, 2024)
Indonesia still has a high prevalence of stunting compared with several other Southeast Asian countries. The National Survey on Nutritional Status in Indonesia in 2022 reported that stunting in Indonesia was 18.5%, while Bangka Regency recorded a stunting prevalence of 16.2%. Feeding under the age of six months has become one of the factors of stunting. This requires concrete effort to handle the problem of stunting. This study aimed to assess the association between prelacteal feeding practices and infant stunting. The research used a cross-sectional design in the Kenangan Health Centre area, Bangka Regency, in May 2023. A sample of 173 infants aged 0-6 months was obtained using cluster random sampling. The height of the selected infants was measured using a lenghtboard and an infantometer. Interviews related to practical feeding were conducted with the parents using a questionnaire. Data were analyzed using Pearson’s correlation test with α= 0,05. The results showed that 14,5% of mothers gave prelacteal food to their infants until 6 months of age. There was a relationship between prelacteal feeding practices and stunting in the Kenanga Health Center working area (p= 0,001; r= -0,663). There was a negative correlation between prelacteal feeding practices and stunting. In conclusion, there is a significant negative relationship between prelacteal feeding practices and infant stunting.